Diving deep into fish allergen immunotherapy: Current knowledge and future directions - Kavita, Reginald *; Nadeem, Kashaf *; Yap, Ervin Zheng Yang *; Amir Hamzah, Abdul Latiff * (Allergy, Asthma and Immunology Association, 2024)
Fish allergy is one of the “big nine” categories of food allergens worldwide, and its prevalence is increasing with the higher demand for this nutritious food source. Fish allergies are a significant health concern as it is a leading cause of food anaphylaxis, accounting for 9% of all deaths from anaphylaxis. The gaps in treating fish allergies at present are the incomplete identification of fish allergens, lack of component-resolved diagnosis of fish allergens in the clinical setting, and the variability in sensitization profiles based on different fish consumption practices. Allergen immunotherapy (AIT) improves tolerance towards accidental consumption of fish and is longer lasting than pharmacotherapy. Current practice or research of fish AIT ranges from the use of whole fish via oral desensitization, to the use of purified recombinant parvalbumin and its hypoallergenic variant, passive IgG immunization, and modifying the allergenicity of parvalbumin by changing the diet of farmed fish. However, the focus of fish allergen-based studies in the context of AIT has been restricted to parvalbumins. More research is required to understand the involvement of other fish allergens, and several other strategies of AIT including peptide vaccines, DNA vaccines, hybrid allergens, and the use of nanobodies that have the capacity to treat multiple allergens have been proposed. For AIT, other important aspects to consider are the route of desensitization, and the biomarkers to assess the success of immunotherapy. Finally, we also address several clinical considerations for fish AIT.